2015
DOI: 10.1016/j.celrep.2015.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Focal MMP-2 and MMP-9 Activity at the Blood-Brain Barrier Promotes Chemokine-Induced Leukocyte Migration

Abstract: Although chemokines are sufficient for chemotaxis of various cells, increasing evidence exists for their fine-tuning by selective proteolytic processing. Using a model of immune cell chemotaxis into the CNS (experimental autoimmune encephalomyelitis [EAE]) that permits precise localization of immigrating leukocytes at the blood-brain barrier, we show that, whereas chemokines are required for leukocyte migration into the CNS, additional MMP-2/9 activities specifically at the border of the CNS parenchyma strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
171
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(186 citation statements)
references
References 45 publications
10
171
0
Order By: Relevance
“…3). As modulators of the tumor microenvironment [23], the matrix metalloproteinases (MMPs) such as MMP-2 and MMP-9 catalyze the proteolysis of epithelial basement membrane, extracellular matrix and components of vascular, thus facilitating cancer invasion, intravasation and extravasation [23,[29][30][31]. Our study showed that metformin treatment down-regulated the expression levels of MMP-2 and MMP-9 in a time-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…3). As modulators of the tumor microenvironment [23], the matrix metalloproteinases (MMPs) such as MMP-2 and MMP-9 catalyze the proteolysis of epithelial basement membrane, extracellular matrix and components of vascular, thus facilitating cancer invasion, intravasation and extravasation [23,[29][30][31]. Our study showed that metformin treatment down-regulated the expression levels of MMP-2 and MMP-9 in a time-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, accumulation of degradation products was blocked by pretreatment of cocultures with the serine protease inhibitor aprotinin, and by MMP inhibitor-2, which blocks the activity of MMP-1, -3, -7, and -9 ( Figure 7, C and D). Notably, MMPs have been implicated in EAE pathogenesis, are secreted by astrocytes, T lymphocytes, and myeloid cells within the PVS, and facilitate leukocyte entry past the GL into the CNS (39). In contrast, degradation product accumulation was not blocked by the cysteine protease inhibitor E-64, or the aspartic protease inhibitor pepstatin.…”
Section: 4mentioning
confidence: 98%
“…Influences on this process could include presentation of CNS antigen in the context of MHC class II within the PVS (8), and dynamic expression of astrocytic cell adhesion molecules and signaling factors (59), as well as induction of local proteases (60)(61)(62). While previous work has revealed a critical role for local proteases, MMP-2 and MMP-9, in activating chemokine pathways within the PVS and inducing immune cells to cross the GL (39,63), our data suggest that local proteases also facilitate immune cell entry by simply digesting the astrocytic TJ barrier. Furthermore, we found that unique patterns of astrocytic and lymphocytic proteases are Collectively, these studies suggest that integral structural components of reactive astrocyte TJs are susceptible to serine protease-and MMP-mediated degradation within the PVS, notably in the presence of activated T lymphocytes.…”
Section: And E) In Contrast Lesions In Mgfapcre Cldn4mentioning
confidence: 99%
“…Correlation coefficient between systemic and local MMP-9 is modest (r=0.572; P<0.01). Systemic MMP-9 might be compromised by systemic atherosclerosis and various pathological conditions, [25][26][27] even though systemic assessment is convenient for clinicians. Therefore, we think that local MMP-9 is more suitable for assessment of coronary-specific inflammatory activity in coronary artery disease.…”
Section: Clinical Implicationmentioning
confidence: 99%